Surveillance of 3′ Noncoding Transcripts Requires FIERY1 and XRN3 in Arabidopsis - Kurihara, Yukio (Genetics Society of America, 2012)
Eukaryotes possess several RNA surveillance mechanisms that prevent undesirable aberrant RNAs from accumulating. Arabidopsis XRN2, XRN3, and XRN4 are three orthologs of the yeast 5′-to-3′ exoribonuclease, Rat1/Xrn2, that function in multiple RNA decay pathways. XRN activity is maintained by FIERY1 (FRY1), which converts the XRN inhibitor, adenosine 3′, 5′-bisphosphate (PAP), into 5′AMP. To identify the roles of XRNs and FRY1 in suppression of non-coding RNAs, strand-specific genome-wide tiling arrays and deep strand-specific RNA-Seq analyses were carried out in fry1 and xrn single and double mutants. In fry1-6, about 2000 new transcripts were identified that extended the 3′ end of specific mRNAs; many of these were also observed in genotypes that possess the xrn3-3 mutation, a partial loss-of-function allele. Mutations in XRN2 and XRN4 in combination with xrn3-3 revealed only a minor effect on 3′ extensions, indicating that these genes may be partially redundant with XRN3. We also observed the accumulation of 3′ remnants of many DCL1-processed microRNA (miRNA) precursors in fry1-6 and xrn3-3. These findings suggest that XRN3, in combination with FRY1, is required to prevent the accumulation of 3′ extensions that arise from thousands of mRNA and miRNA precursor transcripts.